Asnadi Duvvumin Kunfiransi Kishvari-yi : (Kumitahi-yi Ijra'i-yi Duvvumin Kunfransi Kishvari-yi Tudahihai-yi Mubarizi Infisali dar Faransah)
Documents of the Second Country Conference of the Combatant Secessionist Tudahies in France.